Pengetahuan dan Sikap Perawat Gawat Darurat Tentang Tata Laksana Kesiapsiagaan Darurat Pasien dengan HIV-AIDS - Kurniawan, Hendra (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Introduction: the HIV-AIDS epidemic has spread worldwide, including in Indonesia. The Ministry of Health estimates that there were 543,100 PLHIV in 2020. Nurses who provide first-line service must have special skills and attitudes, as well as respect and uphold confidentiality, also the rights and choices of HIV-positive patients. Numerous studies have found that health employees, especially nurses, hold unfavorable views toward patients living with HIV/AIDS. Objective: to assess emergency nurses' knowledge and attitudes for emergency preparedness management of HIV-AIDS patients. Methods: this study employed a cross-sectional descriptive design and was conducted in the emergency departments of two hospitals in Jember Regency. Results: The total number of respondents was 38 emergency nurses, with 14 (36.8%) getting into the good knowledge category and 24 (63.2%) becoming the sufficient knowledge category. In terms of attitude, 16 (42.1%) got into the good attitude and 22 (57.9%) passed the fair attitude category. Conclusion: promoting emergency nurses' knowledge of preparedness management for patients with HIV-AIDS is critical to follow up through training programs, since HIV-AIDS remains a global epidemic of non-natural disasters with a high prevalence, even though the numbers have decreased year over year.